“Honestunes”: Video Musik Kolaborasi Virtual di Masa Pandemi - Sahertian, Grace Carolline (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2023)
The arts and entertainment industry is one of the industries that have been heavily impacted by the Covid-19 pandemic. At the beginning of the pandemic, many musicians lost their stages and musical works that could not be promoted optimally, especially with the implementation of social distancing protocols and large-scale social restrictions. In this